2018
DOI: 10.2519/jospt.2018.8110
|View full text |Cite
|
Sign up to set email alerts
|

Additive Effect of Therapeutic Ultrasound in the Treatment of Plantar Fasciitis: A Randomized Controlled Trial

Abstract: Therapy, level 1b. J Orthop Sports Phys Ther 2018;48(11):847-855. Epub 11 Jul 2018. doi:10.2519/jospt.2018.8110.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 40 publications
0
23
1
2
Order By: Relevance
“…In another randomized controlled trial (RCT), the addition of 1 MHz continuous US, and stretching, led to significant reduction of plantar fasciitis pain, with no significant difference compared with placebo and stretching. 23 In a RCT, US was found to be significantly more effective than shockwave with regard to pain and disability as determined by the Foot Function Index scale. 24 Last, in another study, TUS led to significant pain relief (Visual Analogue Scale [VAS]), improved function, and decreased plantar fascia thickness as measured from magnetic resonance imaging scans in 60 patients with chronic plantar fasciitis.…”
Section: Plantar Fasciitismentioning
confidence: 97%
“…In another randomized controlled trial (RCT), the addition of 1 MHz continuous US, and stretching, led to significant reduction of plantar fasciitis pain, with no significant difference compared with placebo and stretching. 23 In a RCT, US was found to be significantly more effective than shockwave with regard to pain and disability as determined by the Foot Function Index scale. 24 Last, in another study, TUS led to significant pain relief (Visual Analogue Scale [VAS]), improved function, and decreased plantar fascia thickness as measured from magnetic resonance imaging scans in 60 patients with chronic plantar fasciitis.…”
Section: Plantar Fasciitismentioning
confidence: 97%
“…W/cm 2 .Time period of 8 minutes will be followed. 7,15,16 -Additionally, the participants will be given Home Exercise Program. They will be asked to do the program twice a day, which will consist of the same exercises as Group A participants i.e.…”
Section: ) Ultrasound Application Techniquementioning
confidence: 99%
“…However, a randomized, placebo-controlled double-blind trial showed that addition of ultrasound treatment to a stretching program had no positive effect on pain reduction or function. The authors recommended that ultrasound no longer be used in the treatment of PF (40).…”
Section: Conservative Treatmentmentioning
confidence: 99%